2021
DOI: 10.1055/a-1532-5825
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient and Practical Chemoenzymatic Route to (3R,3aR,6R,6aR)-Hexahydrofuro[3,2-b]furan-6-amino-3-ol (6-Aminoisomannide) from Renewable Sources

Abstract: The synthesis of 6-aminoisomannide is easily achieved starting from the renewable, inexpensive and commercially available isosorbide, in 66% overall yield. A biocatalysed highly regioselective acetylation of the 3-endo hydroxyl group of isosorbide was followed by the stereospecific interconversion of the 6-exo hydroxyl group into azido group, through reaction with trifluoromethanesulfonic anhydride followed by nucleophilic displacement of the triflate group by sodium azide. Finally, reduction of the azido grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…While monoderivatization of symmetric isomannide 1 led to one product, reaction of isosorbide 2 afforded a mixture of the two possible isomers 5 and 6 in an ∼1:1 ratio. The nonselective monoderivatization of isosorbide was not an issue, since we were interested in both isomers; a selective derivatization could be easily obtained exploiting an initial selective protection as reported in the literature. , In all cases, pure compounds were obtained in good yields after chromatographic purification, with the only exception of 4a – d , 7a – c that crystallized from the crude and/or were recrystallized after a simple workup.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While monoderivatization of symmetric isomannide 1 led to one product, reaction of isosorbide 2 afforded a mixture of the two possible isomers 5 and 6 in an ∼1:1 ratio. The nonselective monoderivatization of isosorbide was not an issue, since we were interested in both isomers; a selective derivatization could be easily obtained exploiting an initial selective protection as reported in the literature. , In all cases, pure compounds were obtained in good yields after chromatographic purification, with the only exception of 4a – d , 7a – c that crystallized from the crude and/or were recrystallized after a simple workup.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous works, we demonstrated that some isohexide derivatives could be successfully employed as CSAs in NMR studies. 32 , 33 These positive preliminary results prompted us to expand the scope, synthesizing new isohexide derivatives to be employed in NMR enantiodiscrimination studies ( Figure 2 ). In particular, derivatization of the hydroxyl groups as arylcarbamates was chosen to obtain new chiral shift agents that could establish multiple intermolecular interactions, such as π–π interactions through the aromatic groups and dipole–dipole interactions and/or hydrogen bond interactions through the carbamoyl group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These functional groups can be easily derivatized, to obtaining a plethora of derivatives whose properties depend both from the characteristics of the introduced functional groups and from the different stereochemical arrangement of the hydroxyl groups [23,[26][27][28][29]. In previous studies [30][31][32][33][34][35], some of us successfully employed these compounds as starting materials for the synthesis of new chiral auxiliaries [30][31][32][33] and light-emitting materials [34]. These studies highlighted the importance of the chiral backbone, which leads to an interaction between the functional groups linked to the central scaffold, with a great influence on the final properties, both in isomannide 1 and isosorbide 2.…”
Section: Introductionmentioning
confidence: 99%